2024
DOI: 10.1021/acs.chemmater.3c03131
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylate-Protected “Isostructural” Cu20 Nanoclusters as a Model System: Carboxylate Effect on Controlling Catalysis

Bingzheng Yan,
Xuexin You,
Xiongkai Tang
et al.

Abstract: Several recent studies have demonstrated the great promise of ligand-protected atomically precise copper nanoclusters in driving various chemical transformation processes. The insights into key factors in controlling the catalytic performance of copper clusters at the molecular level are highly desirable but difficult to gain. Herein, we report the synthesis and comprehensive characterization of two novel Cu 20 nanoclusters, with the molecular formulae of Se@ Cu 20 (PhSe) 12 (PPh 3 ) 2 (C 6 H 5 COO) 6 (Cu 20 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…The Se 2− in the clusters may be generated in situ by the decomposition of the PhSe − ligands, whose C–Se bonds are broken under the reducing atmosphere. 42,43 Interestingly, during the crystal culture process, Cu 22 -1 and Cu 22 -2 formed crystals with different crystal forms (Fig. S1†), enabling easy separation and subsequent analysis using single-crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…The Se 2− in the clusters may be generated in situ by the decomposition of the PhSe − ligands, whose C–Se bonds are broken under the reducing atmosphere. 42,43 Interestingly, during the crystal culture process, Cu 22 -1 and Cu 22 -2 formed crystals with different crystal forms (Fig. S1†), enabling easy separation and subsequent analysis using single-crystal X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…1–6 With the advancement of sophisticated characterization techniques, numerous metal clusters with atomic-level resolved structures have been reported to date. 7–21 It has been observed that the metal core of many of these clusters shares the same polyhedral units, despite variations in peripheral ligands or metal–ligand motif structures. These polyhedral units encompass an M 13 centered icosahedron, 22–28 an M 6 octahedron, 29–35 an M 13 cuboctahedron 36 and an M 7 decahedron, 37–42 among others, where ‘M’ represents Au, Ag, Cu, or other metal atoms or their mixtures.…”
Section: Introductionmentioning
confidence: 99%